A possible reply from the Schools of Communication to the current crisis and Revolution of the Media - Soria, Carlos (2022)
Schools of Communication need to relocate themselves in the new and blurry scenario of contemporary communication. Many things have changed: technology, the prime material of information, the actors, time and space of information and all media has become really or virtually multimedia At the time of relocation, Schools will have to decide whether to abandon the structure which prolonged the division of the media into an academic site in terms of technological support on which they operated. All of which calls for a rediscovery of which has to be the backbone of future Undergraduate and Graduate programs in Communication.